2022
DOI: 10.1007/s11657-022-01131-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of generic teriparatide and alendronate in Chinese postmenopausal women with osteoporosis: a prospective study

Abstract: Summary The efficacy of generic teriparatide in improving BMD at lumbar spine in patients with osteoporosis was similar to that of alendronate. It provided a new choice for osteoporosis treatment in Chinese population. Introduction To determine whether the efficacy of generic teriparatide is noninferior to alendronate for Chinese postmenopausal women with osteoporosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“… 459 Teriparatide and abaloparatide may cause hypercalcemia and hypercalciuria; therefore, preexisting hypercalcemia, hypercalciuria, and a history of kidney stones are considered contraindications for the use of these drugs. 460 , 461 …”
Section: Strategies and Challenges In The Management Of Osteoporosismentioning
confidence: 99%
“… 459 Teriparatide and abaloparatide may cause hypercalcemia and hypercalciuria; therefore, preexisting hypercalcemia, hypercalciuria, and a history of kidney stones are considered contraindications for the use of these drugs. 460 , 461 …”
Section: Strategies and Challenges In The Management Of Osteoporosismentioning
confidence: 99%
“…Due to its role in regulating bone metabolism and anti-bone resorption, ALN is mainly used in the treatment of osteoporosis in clinical practice, especially for postmenopausal osteoporosis [ 43 ]. Early prophylactic treatment with sodium alendronate in the course of OA disease can reduce the metabolic rate of SB and alleviate the degeneration of articular cartilage, while late administration has no significant effect on articular cartilage, indicating that early treatment to protect SB has a positive role in preventing cartilage destruction [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have detected the coding genes of seven key enzymes in the mevalonate pathway, including Mevalonate kinase (MK), Phosphomevalonate kinase (PMVK), Mevalonate decarboxylase (MVD), Isopentenyl pyrophosphate isomerase (IPI), Geranylgeranyl pyrophosphate synthase 1 (GGPS1), Farnesyl pyrophosphate synthase (FDPS) and Farnesyl-Diphosphate Farnesyltransferase 1 (FDFT1), and three genes of OPG/RANKL/RANK system, a total of 67 tag SNPs, and found that the response to alendronate is significantly associated with the patient’s genetic background. 6–11 Some enzymes in other pathways of bone metabolism also showed high correlation, such as SOST. 6 …”
Section: Introductionmentioning
confidence: 98%